2021
DOI: 10.1186/s12880-020-00545-5
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Pseudoprogression from True Progressionin Glioblastoma Patients after Standard Treatment: A Machine Learning Strategy Combinedwith Radiomics Features from T1-weighted Contrast-enhanced Imaging

Abstract: Background Based on conventional MRI images, it is difficult to differentiatepseudoprogression from true progressionin GBM patients after standard treatment, which isa critical issue associated with survival. The aim of this study was to evaluate the diagnostic performance of machine learning using radiomics modelfrom T1-weighted contrast enhanced imaging(T1CE) in differentiating pseudoprogression from true progression after standard treatment for GBM. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Another important finding with potential clinical implication is that the SVM outperformed radiologists’ classification performance up to 27% in terms of classification accuracy, more profoundly in the multiple time point group. A similar observation is described in a recent study employing radiomic features derived from structural MRI [ 45 ]. However, any generalisation of such comparisons would require confirmation by studies based on larger patient cohorts, prospective design and use of external validation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Another important finding with potential clinical implication is that the SVM outperformed radiologists’ classification performance up to 27% in terms of classification accuracy, more profoundly in the multiple time point group. A similar observation is described in a recent study employing radiomic features derived from structural MRI [ 45 ]. However, any generalisation of such comparisons would require confirmation by studies based on larger patient cohorts, prospective design and use of external validation.…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, the bestperforming features included differences in rCBV, rCBF, T2 kurtosis and subtracted signal intensity on post-contrast T1 sequences on longitudinal MRI studies. Similar features have been identified by previous studies as promising for the differentiation of PsP from PD [44][45][46][47]. Employing machine learning, Akbari et al further demonstrated a correlation between such features, namely enhancement on post-contrast T1 and rCBV, with histologically validated tissue characteristics related to PsP and PD [48].…”
Section: Discussionsupporting
confidence: 64%
“…PP is defined as peritumoral inflammatory tissue that may be erroneously reported as tumor progression or recurrence on MRI images ( 18 ). The PP phenomenon is well documented, and its MRI aspect is justified by its histological findings, consisting of inflammation, neutrophil and macrophage infiltration, reactive astrocytes, high mitotic rate, and neoangiogenesis ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that these characteristics known as radiomic features have the potential to decode tumor phenotypes and predict treatment outcome [4] . Magnetic resonance imaging (MRI)-based radiomics have already demonstrated their promising abilities to predict disease progression [5] , [6] , methylation status [7] , tumor grade [8] and overall survival [9] , [10] for patients with central nervous system malignancies. Magnetic resonance (MR) images are routinely acquired for patients with GBM at baseline and for follow-up.…”
Section: Introductionmentioning
confidence: 99%